Manufacturing method of extra-high density PCB base plate

During the manufacturing process of ultra-high density PCB pads, pre-press, preheat and spray polymer biomass glue for hot pressing, the problems of low surface hardness and high cost are solved, and high performance and low cost are achieved production effect.

CN119497303APending Publication Date: 2025-02-21GUANGXI SUNWAY FOREST PROD CENXI ARTIFICIAL BOARD CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411680485.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

In the prior art, when manufacturing ultra-high density PCB pads, the surface hardness of the board surface is relatively low and the cost is high, and the production process is complicated, making it difficult to ensure stable quality.

Method used

Preheat after pre-pressing, and spray polymer biomass glue on the upper and lower surfaces of the slabs, and finally the process of hot pressing is carried out to improve the internal bonding strength, density and surface hardness of the pad.

Benefits of technology

Effectively improve the mechanical properties of PCB pads, with a density of more than 1020 g/cm3, an internal bonding strength of 2.91MPa, an elastic modulus of 6540MPa, and a surface hardness of more than 84HB, reducing the glue application volume and saving production cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005148217370000091
    Figure BDA0005148217370000091
Patent Text Reader

Abstract

The invention discloses a manufacturing method of an extra-high density PCB base plate, and relates to the technical field of PCB base plate manufacturing. The specific technological process is as follows. Wood raw material selection, peeling, chipping, wood chip screening, water washing, pre-cooking, cooking, hot grinding, glue applying and additive applying, drying, cyclone separation, fiber bin storage, winnowing, paving forming, pre-pressing, preheating, spraying of macromolecular biomass glue on the upper surface and the lower surface of a plate blank, hot pressing, plate turning cooling, curing, sanding and the like and cutting finished products, inspecting and grading, and packaging and warehousing. According to the invention, preheating is carried out after pre-pressing, high-molecular biomass glue is sprayed on the upper surface and the lower surface of the plate blank after preheating, and finally hot pressing is carried out, so that the mechanical properties such as high internal bonding strength, density and surface hardness of the PCB base plate can be effectively improved, and the cost can be saved. Compared with a traditional method, under the condition that the mechanical properties of a finished product are the same, 20-30 kg / m < 3 > of glue can be saved by adopting the method, the production cost is saved, and large-scale production is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of PCB pad preparation, and in particular to a method for manufacturing an ultra-high-density PCB pad. Background Art

[0002] With the continuous development of electronic technology, the demand for ultra-high-density PCB is growing. Ultra-high-density PCB has the characteristics of high line density, small aperture, and many layers, which puts higher requirements on the performance of the pad. Research on ultra-high-density PCB pad production technology can meet the development needs of ultra-high-density PCB and promote the progress of the electronics industry.

[0003] Fiberboard, also known as density board, has the advantages of uniform material, small vertical and horizontal strength difference, and not easy to crack. It can be used as a type of PCB pad. Fiberboard is a man-made board made of wood fiber or other plant fiber as raw materials, and urea-formaldehyde resin or other suitable adhesives are applied. Adhesives and / or additives can be applied during the manufacturing process. At present, based on the requirements of PCB pad characteristics, the existing fiberboard can meet the general PCB pad requirements, but the pad required for higher precision PCB has higher surface hardness and better flatness, and ultra-high density PCB came into being.

[0004] There are many research results in the production technology of ultra-high-density PCB pads. Researchers have conducted in-depth explorations on the material selection, processing technology and performance optimization of pads. For example, in terms of materials, new high-strength, high-flatness and heat-resistant materials are constantly tried to meet the strict requirements of ultra-high-density PCBs for pads. In terms of processing technology, precision processing equipment and advanced surface treatment technology are used to ensure the dimensional accuracy and surface quality of the pads. At the same time, by optimizing quality control measures, the size, flatness and strength of the pads are strictly tested to improve the reliability of the product.

[0005] However, there are still some defects and deficiencies in the production technology of ultra-high-density PCB pads: (1) The low surface hardness of the board and the high cost are prominent problems. The existing technology mainly adopts high-performance materials, increases the amount of glue applied and UV processing to achieve the requirements of ultra-high-density PCB pads. The application of some high-performance materials and complex processing technology make the production cost of the pads high. When the amount of glue applied is increased, the glue amount is generally as high as 260-270kg / m 3 , which leads to an increase in cost. (2) The manufacturing is difficult. The pad production process has extremely high requirements for precision and process control, such as ensuring the flatness of the material, uniform thickness, and precise molding, which increases the complexity and difficulty of production and easily leads to unstable quality.

[0006] In summary, the present invention provides a method for manufacturing an ultra-high-density PCB pad. Summary of the invention

[0007] In view of the above shortcomings, the present invention provides a method for manufacturing an ultra-high-density PCB pad, which solves the problem of insufficient surface hardness and high cost of preparing an ultra-high-density PCB pad. The specific technical solution is as follows:

[0008] A method for manufacturing an ultra-high-density PCB pad includes the following process flow: selection of wood raw materials - peeling - chipping - wood chip screening - water washing - pre-cooking - cooking - hot grinding - gluing and applying additives - drying - cyclone separation - fiber storage - air selection - paving and forming - pre-pressing - preheating - hot pressing - board cooling - curing - sanding - cutting of finished products - inspection and grading - packaging and warehousing, and also includes the step of spraying polymer biomass glue on the upper and lower surfaces of the slab before hot pressing.

[0009] Furthermore, the spraying amount of the polymer biomass glue on the upper surface of the board blank is 4-6g / m 2 The spraying amount of the polymer biomass glue on the lower surface of the board is 1-3g / m 2 .

[0010] Furthermore, the pre-cooking temperature is 85-95° C. and the time is 10-30 min.

[0011] Furthermore, the cooking pressure is 8-10 bar, the time is 4-6 min, and the pressure difference is 0.1-0.5 bar.

[0012] Furthermore, the pressure of the hot grinding is 8-10 bar and the temperature is 160-175°C; 3-4.5 kg / m 3 Waterproofing agent should be used together.

[0013] Furthermore, the gluing is to apply high-strength urea-formaldehyde resin glue, and the application amount is 230-240kg / m 3 The additive is a curing agent, and the amount of the curing agent added is 1-3kg / m 3 .

[0014] Furthermore, the drying is to dry the wood fiber to a moisture content of 8-10%.

[0015] Furthermore, the preheating is to heat the slab by hot steam, and the preheating torque is 85-110N.m.

[0016] Furthermore, the hot pressing is to hot press the slab by a hot press, the hot pressing temperature is 205°C, and the hot pressing pressure is 500-650N / cm 2 , the heat pressure factor is 7.5-8.0s / mm.

[0017] The present invention also provides an ultra-high-density PCB pad produced by the above-mentioned production method.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] 1. The present invention performs preheating after pre-pressing, sprays polymer biomass glue on the upper and lower surfaces of the slab after preheating, and finally performs hot pressing, which can not only effectively improve the mechanical properties of the PCB pad such as internal bonding strength, density and surface hardness, but also save costs. Compared with the traditional method, under the condition of the same mechanical properties of the finished product, the method of the present invention can save 20-30kg / m 3 The amount of glue applied saves production costs and is conducive to large-scale production.

[0020] 2. Since the slab is still relatively fluffy after pre-pressing, if hot pressing is performed directly at this time, the fiber material will rebound to a certain extent. Therefore, according to the traditional method (pre-pressing + hot pressing), the internal bonding strength, density and surface hardness of the product are difficult to meet the requirements of ultra-high density. The present invention adopts the mode of pre-pressing + preheating + spraying polymer biomass glue on the slab surface + hot pressing. After preheating, the surface and internal temperatures of the slab are uniform. At this time, spraying polymer biomass glue on the slab surface can well bond the fiber materials on the surface of the slab together, preliminarily increasing the maximum density of the slab surface, so that the core fiber material of the slab is further fixed to prevent excessive rebound. On this basis, hot pressing is performed to obtain a finished product with high internal bonding strength, density and surface hardness. The PCB pad prepared by the method of the present invention has excellent mechanical properties and a density of more than 1020 g / cm 3 The internal bonding strength can reach 2.91MPa, the elastic modulus can reach 6540MPa, and the surface hardness can reach above 84HB, which are all higher than the general PCB pads. It is not easy to crack or deform during use, and meets the requirements of ultra-high-density PCB pads. DETAILED DESCRIPTION

[0021] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments.

[0022] It should be noted that the polymer biomass glue involved below comes from Guangxi Zhishan New Material Technology Co., Ltd., model A6-8, and the high-strength urea-formaldehyde resin glue was purchased from Guangxi Wuzhou Weinuo Chemical Co., Ltd.

[0023] Example 1

[0024] The manufacturing method of a super-high-density PCB pad in this embodiment includes the following process flow: selection of wood raw materials - peeling - chipping - wood chip screening - water washing - pre-cooking - cooking - hot grinding - glue and additive application - drying - cyclone separation - fiber storage - wind selection - paving and forming - pre-pressing - preheating - spraying high-molecular biomass glue on the top and bottom of the slab - hot pressing - board cooling - health preservation - sanding - cutting finished products - inspection and grading - packaging and storage. Specifically:

[0025] (1) Selection of wood materials: Pure miscellaneous wood with a storage period of 20 days should be selected as the wood materials. Purchased wood chips that have been stored for more than 10 days should not be used to avoid differences in wood properties due to differences in the properties of different raw materials, which may cause greater internal stress in the board, reduce internal bonding strength, density and surface hardness, and cause deformation.

[0026] (2) Peeling - Chipping - Chip Screening: After the selected wood raw materials are peeled, they are made into wood chips by a chipper. The wood chips are screened and the oversized or undersized wood chips are removed to ensure the quality of the chips. The length and width of qualified wood chips should not exceed 40 mm, and the thickness should not exceed 15 mm.

[0027] (3) Water washing: Wash the wood chips with water to remove impurities from the raw materials, avoid damage to the drill bit during use, reduce impurities on the electronic circuit pad, and ensure the flatness of the board surface.

[0028] (4) Pre-cooking: The washed wood chips are pre-cooked at a temperature of 85°C for 30 min to obtain preliminarily softened wood chips;

[0029] (5) Steaming: The preliminarily softened wood chips are steamed, and the pressure of the steaming cylinder is set to 8 bar, the time is 6 minutes, and the pressure difference is 0.1 bar.

[0030] (6) Hot grinding: The cooked wood chips are placed in the grinding chamber for hot grinding. The pressure of the hot grinding is 8 bar and the temperature is 175°C. At the same time, the waterproofing agent paraffin is added to the grinding chamber at an amount of 3 kg / m 3 ; The opening of the spray valve and the energy consumption of the hot mill are adjusted according to the hot mill speed and fiber quality. If the set requirements are not met, the grinding disc should be replaced or other specifications should be converted; the crude fiber ratio is controlled at 1.3%; fine and uniform wood fibers can be obtained after hot milling;

[0031] Specifically, the fiber quality requirements for ultra-high-density PCB pads are: fibers larger than 300 mesh account for 1.5% of the total fiber weight, fibers between 100 mesh and 300 mesh account for ≥68.5% of the total fiber weight, and fibers less than 100 mesh account for ≤30% of the total fiber weight.

[0032] (7) Gluing and applying additives: Add high-strength urea-formaldehyde resin glue to the wood fibers obtained by hot grinding, with an application amount of 240 kg / m3 , curing agent 1kg / m 3 , black dye 14.5kg / m 3 High-strength urea-formaldehyde resin glue and curing agent are sprayed through a high-pressure glue application system, which can improve the uniformity of glue application, increase the contact area between fiber and urea-formaldehyde glue, and reduce the amount of glue applied.

[0033] (8) Drying: The wood fiber is dried using low-temperature steam, the temperature of the low-temperature steam is 130°C, the flow rate is 28m / s, and the air volume is 300,000m 3 , dried until the moisture content of the wood fiber is 8%.

[0034] (9) Sorting: After drying, the fibers are sorted and screened to obtain fibers of appropriate size, and the coarse fibers and impurities are discarded.

[0035] (10) Fiber storage bin: Fiber storage time: In summer (fiber temperature exceeds 42°C), if the machine is shut down for more than 15 minutes, it will be marked as old material; in other seasons, if the machine is shut down for more than 25 minutes, it will be marked as old material; the marking time of old material depends on the specific requirements of the material level in the bin, and the minimum is 15 minutes; when marking old material, the surface hardness of each board should be tested after sanding; this is used to determine the number of old materials to be downgraded. If the thickness and density of the production process are obviously beyond the process range, the number of tests needs to be increased for qualification determination, and downgrade will be carried out if there is a quality risk.

[0036] (11) Laying and forming: The glued fibers are laid through a silo and mechanical laying is used to ensure the uniformity of laying to obtain a slab.

[0037] (12) Pre-compression: The paved slab is compressed and exhausted at a corresponding compression ratio, with a pre-compression torque of 80 N.m.

[0038] (13) Preheating: The pre-pressed slab is heated by hot steam, with a preheating torque of 85 N.m.

[0039] (14) Hot pressing: Before hot pressing, spray an appropriate amount of polymer biomass glue on the upper and lower surfaces of the slab. The spraying amount of polymer biomass glue on the upper surface of the slab is 4g / m 2 The spraying amount of polymer biomass glue on the lower surface of the board is 1g / m 2 The slab is hot pressed by a hot press, the hot pressing temperature is 205°C and the hot pressing pressure is 500N / cm 2 , the hot pressing factor is 7.5s / mm. When the core layer of the board is fully cured, the curve is smooth, and the saw edge is dense, the temperature of the last 3-4 zones of the press should be adjusted as low as possible in summer to avoid over-baking of the board, increase the pre-pressing torque, and increase the preheating dew point to ensure that the strength of the slab meets the requirements. The press inlet height is 1mm higher than the slab height to prevent the back spray from the bottom of the board to form fiber white spots on the bottom of the board.

[0040] (15) Turn over and cool the board - cure - sanding - inspection and grading - packaging and storage: The hot-pressed board is turned over and cooled, and the curing time is less than 24 hours. In order to ensure the fine and smooth surface of the board after sanding, a sanding belt is used to use a five-step sanding process of 100 mesh, 100 mesh, 120 mesh, 150 mesh, and 180 mesh. The substrate after sanding is inspected and graded, and the sorting time is ≤24 hours, and then it is packaged and stored.

[0041] Example 2

[0042] The manufacturing method of a super-high-density PCB pad in this embodiment includes the following process flow: selection of wood raw materials - peeling - chipping - wood chip screening - water washing - pre-cooking - cooking - hot grinding - glue and additive application - drying - cyclone separation - fiber storage - wind selection - paving and forming - pre-pressing - preheating - spraying high-molecular biomass glue on the top and bottom of the slab - hot pressing - board cooling - health preservation - sanding - cutting finished products - inspection and grading - packaging and storage. Specifically:

[0043] (1) Selection of wood materials: Pure miscellaneous wood with a storage period of 60 days should be selected as the wood materials. Purchased wood chips that have been stored for more than 10 days should not be used to avoid differences in wood properties due to differences in the properties of different raw materials, which may cause greater internal stress in the board, reduce internal bonding strength, density and surface hardness, and cause deformation.

[0044] (2) Peeling - Chipping - Chip Screening: After the selected wood raw materials are peeled, they are made into wood chips by a chipper. The wood chips are screened and the oversized or undersized wood chips are removed to ensure the quality of the chips. The length and width of qualified wood chips should not exceed 40 mm, and the thickness should not exceed 15 mm.

[0045] (3) Water washing: Wash the wood chips with water to remove impurities from the raw materials, avoid damage to the drill bit during use, reduce impurities on the electronic circuit pad, and ensure the flatness of the board surface.

[0046] (4) Pre-cooking: The washed wood chips are pre-cooked at a temperature of 90°C for 15 min to obtain preliminarily softened wood chips;

[0047] (5) Steaming: The preliminarily softened wood chips are steamed, and the pressure of the steaming cylinder is set to 8.5 bar, the time is 4 minutes, and the pressure difference is 0.2 bar.

[0048] (6) Hot grinding: The cooked wood chips are placed in the grinding chamber for hot grinding. The pressure of the hot grinding is 8.5 bar and the temperature is 168°C. At the same time, the waterproofing agent paraffin is added to the grinding chamber at an amount of 3.5 kg / m 3; The opening of the spray valve and the energy consumption of the hot mill are adjusted according to the hot mill speed and fiber quality. If the set requirements are not met, the grinding disc should be replaced or other specifications should be converted; the crude fiber ratio is controlled at 1.7%; fine and uniform wood fibers can be obtained after hot milling;

[0049] Specifically, the fiber quality requirements for ultra-high-density PCB pads are: fibers larger than 300 mesh account for 1.5% of the total fiber weight, fibers between 100 mesh and 300 mesh account for ≥68.5% of the total fiber weight, and fibers less than 100 mesh account for ≤30% of the total fiber weight.

[0050] (7) Gluing and applying additives: Add high-strength urea-formaldehyde resin glue to the wood fibers obtained by hot grinding, with an application amount of 235 kg / m 3 , curing agent 2kg / m 3 , black dye 15.5kg / m 3 High-strength urea-formaldehyde resin glue and curing agent are sprayed through a high-pressure glue application system, which can improve the uniformity of glue application, increase the contact area between fiber and urea-formaldehyde glue, and reduce the amount of glue applied.

[0051] (8) Drying: The wood fiber is dried using low-temperature steam, the temperature of the low-temperature steam is 130°C, the flow rate is 28m / s, and the air volume is 300,000m 3 , dried until the moisture content of the wood fiber is 10%.

[0052] (9) Sorting: After drying, the fibers are sorted and screened to obtain fibers of appropriate size, and the coarse fibers and impurities are discarded.

[0053] (10) Fiber storage bin: Fiber storage time: In summer (fiber temperature exceeds 42°C), if the machine is shut down for more than 15 minutes, it will be marked as old material; in other seasons, if the machine is shut down for more than 25 minutes, it will be marked as old material; the marking time of old material depends on the specific requirements of the material level in the bin, and the minimum is 15 minutes; when marking old material, the surface hardness of each board should be tested after sanding; this is used to determine the number of old materials to be downgraded. If the thickness and density of the production process are obviously beyond the process range, the number of tests needs to be increased for qualification determination, and downgrade will be carried out if there is a quality risk.

[0054] (11) Laying and forming: The glued fibers are laid through a silo and mechanical laying is used to ensure the uniformity of laying to obtain a slab.

[0055] (12) Pre-compression: The paved slab is compressed and exhausted at a corresponding compression ratio, with a pre-compression torque of 100 N.m.

[0056] (13) Preheating: The pre-pressed slab is heated by hot steam, with a preheating torque of 110 N.m.

[0057] (14) Hot pressing: Before hot pressing, spray an appropriate amount of polymer biomass glue on the upper and lower surfaces of the slab. The spraying amount of polymer biomass glue on the upper surface of the slab is 5g / m 2 The spraying amount of polymer biomass glue on the lower surface of the board is 2g / m 2 The slab is hot pressed by a hot press, the hot pressing temperature is 205°C and the hot pressing pressure is 600N / cm 2 , the hot pressing factor is 8.0s / mm. When the core layer of the board is fully cured, the curve is smooth, and the saw edge is dense, the temperature of the last 3-4 zones of the press should be lowered as much as possible in summer to avoid over-baking of the board, increase the pre-pressing torque, and increase the preheating dew point to ensure that the strength of the slab meets the requirements. The press inlet height is 1mm higher than the slab height to prevent the back spray from the bottom of the board to form fiber white spots on the bottom of the board.

[0058] (15) Turn over and cool the board - cure - sanding - inspection and grading - packaging and storage: The hot-pressed board is turned over and cooled, and the curing time is less than 24 hours. In order to ensure the fine and smooth surface of the board after sanding, a sanding belt is used to use a five-step sanding process of 100 mesh, 100 mesh, 120 mesh, 150 mesh, and 180 mesh. The substrate after sanding is inspected and graded, and the sorting time is ≤24 hours, and then it is packaged and stored.

[0059] Comparative Example 1: There is no step of spraying high molecular biomass glue on the upper and lower sides of the slab, but the process is carried out according to pre-pressing-preheating-hot pressing, that is, hot pressing is directly carried out after pre-pressing and preheating. The other steps are the same as those in Example 1.

[0060] Comparative Example 2: There is no preheating step, but the process is carried out according to pre-pressing-spraying polymer biomass glue on the upper and lower sides of the slab-hot pressing, that is, after pre-pressing, the polymer biomass glue is directly sprayed on the upper and lower sides of the slab without preheating. The other steps are the same as those in Example 1.

[0061] Comparative Example 3: The polymer biomass glue is not sprayed on the surface of the slab, but is added together with the high-strength urea-formaldehyde resin glue during the gluing in step (7), and the added amount is the same as that in Example 1. The other steps are the same as those in Example 1.

[0062] The thickness of the pads prepared by the above-mentioned embodiments and comparative examples is 2-3 mm.

[0063] The fiberboards prepared in the above-mentioned Examples 1 to 2 and Comparative Examples 1 to 3 were tested according to the standard requirements of GB / T 11718-2021. Five samples were taken from each group for testing and the average value was taken. The results are shown in Table 1 below.

[0064] Table 1 Comparison of mechanical properties of each group of pads

[0065] project Example 1 Example 2 Comparative Example 1 Comparative Example 2 Comparative Example 3 Moisture content (%) 5.7 6.1 5.2 5.5 5.3 <![CDATA[Density (g / cm 3 )]]> 1020 1023 1016 1019 1018 Water absorption thickness expansion rate (%) 15.9 15.7 17.1 16.3 16.5 Internal bonding strength (MPa) 2.91 2.95 2.01 2.88 2.85 Static bending strength (MPa) 86.0 86.8 80.0 84.4 82.9 Surface bonding strength (MPa) 3.45 3.56 3.22 3.42 3.40 Elastic modulus (MPa) 6537 6540 6215 6488 6420 Surface hardness (HB) 84 85 80 83 82

[0066] The table above shows that compared with not spraying polymer biomass glue on the surface of the slab, spraying polymer biomass glue on the surface of the slab can effectively improve the internal bonding strength, static bending strength, surface bonding strength, elastic modulus, density and surface hardness of the PCB pad. At the same time, preheating first, spraying polymer biomass glue on the surface of the slab, and finally pre-pressing are indispensable. Only the mode of "preheating + spraying polymer biomass glue on the surface of the slab + pre-pressing" can improve the mechanical properties of the PCB pad, so that the overall surface hardness of the prepared PCB pad is good, high strength, moisture-proof, not easy to deform or break, and meet the mechanical requirements of ultra-high density PCB pads.

[0067] Comparative Example 4: The spraying amount of polymer biomass glue on the upper surface of the board is 3g / m 2 The spraying amount of polymer biomass glue on the lower surface of the board is 2g / m 2 (Same as Example 2). Other steps are the same as Example 2.

[0068] Example 2: The spraying amount of polymer biomass glue on the upper surface of the board is 5g / m 2 The spraying amount of polymer biomass glue on the lower surface of the board is 2g / m 2 .

[0069] 2 Comparative Example 5: The spraying amount of polymer biomass glue on the upper surface of the board is 7g / m 2 The spraying amount of high molecular weight biomass glue on the lower surface of the board is 2g / m 2 (Same as Example 2). Other steps are the same as Example 2.

[0070] The thickness of the pads prepared by the methods of Comparative Examples 4 and 5 is 2-3 mm.

[0071] The fiberboards prepared in Example 2, Comparative Example 4 and Comparative Example 5 were tested according to the standard requirements of GB / T 11718-2021. Five samples were taken from each group for testing and the average value was taken. The results are shown in Table 2 below.

[0072] Table 2 Comparison of mechanical properties of each group of pads

[0073] project Example 2 Comparative Example 4 Comparative Example 5 Moisture content (%) 6.1 5.5 5.3 <![CDATA[Density (g / cm 3 )]]> 1023 1019 1014 Water absorption thickness expansion rate (%) 15.7 16.5 16.9 Internal bonding strength (MPa) 2.95 2.88 2.81 Static bending strength (MPa) 86.8 85.7 85.5 Surface bonding strength (MPa) 3.56 3.42 3.40 Elastic modulus (MPa) 6540 6520 6518 Surface hardness (HB) 85 82 80

[0074] The above table shows that the amount of polymer biomass glue sprayed on the surface of the board will also have a certain impact on the performance of the finished product. After repeated experiments, the applicant found that when the amount of polymer biomass glue sprayed on the upper surface of the board is 4-6g / m 2 When the spraying amount of polymer biomass glue on the lower surface of the board is within the range of 1-3g / m 2 When the range is smaller, the overall surface hardness, strength and stability of the PCB pad are better.

[0075] In order to illustrate that the present invention can reduce costs, the applicant has made a cost comparison, wherein the comparison group uses the prior art method to prepare the pad, uses high-strength urea-formaldehyde resin adhesive in the gluing step, and does not spray polymer biomass glue on the upper and lower surfaces of the slab. The other preparation processes are the same as those in Example 2. The thickness and performance of the pad prepared by the comparison group are basically the same as those of the pad in Example 2. Cost accounting is performed on the use of raw materials, and the results are shown in Table 3:

[0076] Table 3 Cost comparison between the present invention and the prior art

[0077]

[0078]

[0079] Note: The spraying amount of polymer biomass glue on the upper surface of the board in Example 2 is 5g / m 2 The spraying amount of polymer biomass glue on the lower surface of the board is 2g / m 2 The total amount of the upper and lower surfaces converted to cubic meters is 0.71 kg / m 3 .

[0080] As shown in Table 3, the method of the present invention can save 41.61 yuan per square meter in preparing ultra-high-density PCB pads compared with the traditional preparation method, which is very conducive to large-scale production.

[0081] In summary, the present invention performs preheating after pre-pressing, sprays polymer biomass glue on the upper and lower surfaces of the slab after preheating, and finally performs hot pressing, which can not only effectively improve the mechanical properties of the PCB pad such as internal bonding strength, density and surface hardness, but also save costs. Compared with the traditional method, under the condition of the same mechanical properties of the finished product, the method of the present invention can save 20-30kg / m 3 The amount of glue applied saves production costs and is conducive to large-scale production. And because the slab is still relatively fluffy after pre-pressing, if hot pressing is directly performed at this time, the fiber material will rebound to a certain extent. Therefore, according to the traditional method (pre-pressing + hot pressing), the internal bonding strength, density and surface hardness of the product are difficult to meet the requirements of ultra-high density. The present invention adopts a mode of pre-pressing + preheating + spraying polymer biomass glue on the surface of the slab + hot pressing. After preheating, the surface and internal temperatures of the slab are uniform. At this time, spraying polymer biomass glue on the surface of the slab can well bond the fiber materials on the surface of the slab together, preliminarily increasing the maximum density of the slab surface, so that the core layer fiber material of the slab is further fixed to prevent excessive rebound, and then hot pressing is performed on this basis to obtain a finished product with high internal bonding strength, density and surface hardness. The PCB pad prepared by the method of the present invention has excellent mechanical properties and a density of more than 1020 g / cm 3The internal bonding strength can reach 2.91MPa, the elastic modulus can reach 6540MPa, and the surface hardness can reach above 84HB, which are all higher than the general PCB pads. It is not easy to crack or deform during use, and meets the requirements of ultra-high-density PCB pads.

[0082] The foregoing description of specific exemplary embodiments of the present invention is for the purpose of illustration and demonstration. These descriptions are not intended to limit the present invention to the precise form disclosed, and it is clear that many changes and variations can be made based on the above teachings. The purpose of selecting and describing the exemplary embodiments is to explain the specific principles of the present invention and its practical application, so that those skilled in the art can realize and utilize various different exemplary embodiments of the present invention and various different selections and changes. The scope of the present invention is intended to be limited by the claims and their equivalents.

Claims

1. A method for manufacturing an ultra-high-density PCB pad, comprising the following process flow: selection of wood raw materials - peeling - chipping - wood chip screening - water washing - pre-cooking - cooking - hot grinding - sizing and applying additives - drying - cyclone separation - fiber storage - air selection - paving and forming - pre-pressing - preheating - hot pressing - flap cooling - health preservation - sanding - cutting finished products - inspection and grading - packaging and warehousing, characterized in that, The method also includes the step of spraying high molecular biomass glue on the upper and lower surfaces of the slab before hot pressing.

2. The method for manufacturing a super high density PCB pad according to claim 1, characterized in that: The spraying amount of the polymer biomass glue on the upper surface of the board blank is 4-6g / m 2 The spraying amount of the polymer biomass glue on the lower surface of the board is 1-3g / m 2 .

3. The method for manufacturing a super high density PCB pad according to claim 1, characterized in that: The pre-cooking temperature is 85-95° C. and the pre-cooking time is 10-30 minutes.

4. The method for manufacturing a super high density PCB pad according to claim 1, characterized in that: The cooking pressure is 8-10 bar, the cooking time is 4-6 minutes, and the pressure difference is 0.1-0.5 bar.

5. The method for manufacturing an ultra-high-density PCB pad according to claim 1, characterized in that: The pressure of the hot grinding is 8-10 bar and the temperature is 160-175°C. During the hot grinding, 3-4.5 kg / m 3 Waterproofing agent should be used together.

6. The method for manufacturing an ultra-high-density PCB pad according to claim 1, characterized in that: The glue application is to apply high-strength urea-formaldehyde resin glue, and the application amount is 230-240Kg / m 3 The additive is a curing agent, and the amount of the curing agent added is 1-3kg / m 3 .

7. The method for manufacturing an ultra-high-density PCB backing plate according to claim 1, characterized in that: The drying process is to dry the wood fiber to a moisture content of 8-10%.

8. The method for manufacturing an ultra-high-density PCB pad according to claim 1, characterized in that: The preheating is to heat the slab by hot steam, and the preheating torque is 85-110N.m.

9. The method for manufacturing an ultra-high-density PCB backing plate according to claim 1, characterized in that: The hot pressing is to hot press the slab by a hot press, the hot pressing temperature is 205°C, and the hot pressing pressure is 500-650N / cm 2 , the heat pressure factor is 7.5-8.0s / mm.

10. An ultra-high-density PCB pad manufactured by the manufacturing method according to any one of claims 1 to 9.